A method for constructing connected dominating set for consensus in ad hoc wireless network. (22nd February 2022) - Huang, Qingdong; Zhou, Yun; Liu, Qing
This paper proposes a concise-connected dominating set (C-CDS) algorithm of constructing connected dominating set (CDS) for ad hoc wireless networks. By introducing the eigenvector centrality value related to topology-information as unique id number of node, this method can reduce the omitted nodes caused by randomness of node numbering, retain the dominant node with high influence and remove more dominating nodes with small influence. In addition, adding and perfecting reduction rules further simplify the CDS after the reduction of original two rules, which can significantly reduce the size of connected dominating set compared with the existing methods at a small computational cost. Finally, we also propose a fast method for consensus which can reach consensus in one round based on CDS, with the final consensus result shared to the entire network. Simulation results verify that there is better performance in generating C-CDS and consensus than the existing algorithm.